Evaluation of red rose extract as a natural dye: a fourmethod approach to color vision analysis - Rodzali, Nur Nadirah; Abdullah, Siti Nur Azmu’i; Tengku Amri, Tengku Nur Alia Masyitah; Nor Apindi, Noor Hafizah; Shamsul Nizam, Saufiah Alawiyah; Alauddin, Nurnajaa Farzanah; Hanifah, Maisarah; Ismail, Muhammad Amiruddin (2025)
Due to their environmentally benign qualities, natural dyes are growing ever more popular as longterm substitutes for synthetic dyes. This study investigates the extraction of natural dye from rose petals and its application to cotton fabric, aiming to evaluate its colour vision. Rose petals were chosen for their abundant availability and potential as a sustainable dye source. As concerns about the negative effects of synthetic colorants on the environment and human health grow, natural dyes offer low toxicity, biodegradability, and renewable sourcing. Four extraction techniques (acetic acid, sodium hydroxide, ethanol and distilled water) were applied to fresh rose petals, and the extracted dyes were tested on cotton fabric. The color properties of the dye extracted from rose petals varied significantly depending on the extraction medium. Acidic extraction yielded the most vibrant and stable purple hue. In contrast, alkaline extraction resulted in a dull orange-brown tone that faded overtime. Aqueous extraction produced the lightest color, a pale pink, while alcohol-based extraction generated a medium brown shade. These findings suggest that the extraction medium plays a crucial role in determining both the intensity and stability of the color obtained from rose petals. These results are in keeping with earlier studies that demonstrated anthocyanin pigments are more stable when extracted in an acidic environment but deteriorate when extracted in an alkaline environment.